Metode Analytical Hierarcy Process Untuk Menentukan Sekolah Sepak Bola Di Sukabumi - Fahrizal Fahrizal; Iwan Rizal Setiawan; Prajoko (STEKOM PRESS, 2022)
Football School (SSB) is a supporting facility for children who have potential in the field of soccer in order to improve their skills. Football is a large ball game played in teams with a team of 10 players and 1 goalkeeper. In this game, teamwork is an important value that must be possessed to achieve competitive victory. However, along with problems in the form of discrepancies in operational standardization in soccer schools, causing negative public perceptions of the existence of this school. Therefore, a research was conducted to build a decision-making model in determining the choice of soccer schools in accordance with legal standards for children, namely using the Analytical Hierarchy Process (AHP) method. The AHP method is one method that can solve a problem because there is a hierarchy where there are several important aspects, namely Objects, Criteria, Sub Criteria, and Alternatives. By combining data and knowledge, it can increase effectiveness in decision makers. It is hoped that in the future, this research can help the community to support their children in the field of soccer by determining the appropriate soccer school.